Optimization of low‐cost biosurfactant produced by Bacillus subtilis SASCBT01 and their environmental remediation potential. (13th October 2020) - Selvam, K.; Senthilkumar, B.; Selvankumar, T.
Abstract: The present research aims to enhance the biosurfactant (BS) production using agricultural by‐products as a low‐cost substrate with the statistical approach. BS production from Bacillus subtilis SASCBT01 was carried out with four different variables such as pH, incubation time, cassava peel waste (CPW) and palmira sprout (PS). The model expected the highest emulsification activity of 65 ± 1·2% after 96‐h incubation with 3·0 g l −1 of CPW and PS at pH 7·0. The SASCBT01 strain‐based BS was successful at retrieving up to 18% and the highest Pb removal rates were found at 65%. These BS have considered high quality in bioremediation applications. Abstract : Significance and impact of the study: Bacillus subtilis SASCBT01, an indigenous isolate, was employed for the production of promising biosurfactant using agricultural by‐products as the substrate. Biosurfactant production was optimized through response surface methodology–Box–Behnken design (RSM‐BBD). This study report that the biosurfactants produced are promising eco‐friendly and economical agents for metal degradation and oil‐recovery applications.